2016
DOI: 10.3892/ijo.2016.3624
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic acid sensitizes lung cancer cells to chemotherapeutic agents and anoikis via integrin β1/β3 downregulation

Abstract: Chemotherapeutic failure and metastasis are the main causes of high mortality rate in lung cancer. Alteration of cellular redox status in response to endogenous stimuli or exogenous compounds has a significant impact on cell signaling and behavior. Herein we divulge for the first time that lung cancer cells exposed to α-lipoic acid (LA) resulted in a higher level of cellular superoxide anion (O2·-) and hydrogen peroxide (H2O2), and such an increase of the specific reactive oxygen species (ROS) downregulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Cancer metastasis is the multistep process of cancer cells spreading from their original site to other distant sites of the body [ 32 – 34 ]. During metastasis, cancer cells in an anchorage-independent condition are likely to die in the process of anoikis, a detachment-induced apoptosis; however, metastatic cells utilize several mechanisms to escape anoikis and consequently grow at distant sites [ 22 , 35 , 36 ]. Among several potentiating factors of metastasis, the transition of epithelial to mesenchymal phenotype, known as EMT [ 6 , 37 , 38 ], has garnered most attention [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer metastasis is the multistep process of cancer cells spreading from their original site to other distant sites of the body [ 32 – 34 ]. During metastasis, cancer cells in an anchorage-independent condition are likely to die in the process of anoikis, a detachment-induced apoptosis; however, metastatic cells utilize several mechanisms to escape anoikis and consequently grow at distant sites [ 22 , 35 , 36 ]. Among several potentiating factors of metastasis, the transition of epithelial to mesenchymal phenotype, known as EMT [ 6 , 37 , 38 ], has garnered most attention [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of integrin β1 and β3 influences with various aggressive behaviors in cancer cells [ 36 , 37 ]. Recent study revealed that the diminution of β1 and β3 integrins suppresses survival and growth under detachment condition in human lung cancer cells [ 38 ]. Herein, suppression on integrin survival pathway in lung cancer cells induced by avicequinone B was elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with the EDTA/EGTAbased pulmonary chelation therapy, modulation of integrins expression using integrins inhibitors or anti-integrin antibodies could also serve as a mechanism to treat COVID-19 patients ( Henderson et al, 2013 , Hatley et al, 2018 , Sigrist et al, 2020 ). The expression of such integrins can be down regulated by modulation of intracellular redox ions such as superoxide anion (O 2 •− ) and H 2 O 2 ( Puchsaka et al, 2016 ). Besides this, some bioactive compounds/molecules such as Ouabain are also known to affect integrins expression in lung cells (Ninsontia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%